An Integrated Fuzzy Dephi and Interval-Valued Intuitionistic Fuzzy M-Topsis Model for Design Concept Selection - Aikhuele, Daniel Osezua; Faiz, Mohd Turan (PJSOR, 2017)
In this paper, the Modified Technique for Order Preference by Similarity to the Ideal Solution (M-TOPSIS) model has been extended into the intuitionistic fuzzy environment. By applying the improved score function first, to represent the aggregated effect of positive and negative evaluations in the performance ratings of the alternatives based on interval-valued intuitionistic fuzzy set (IVIFS) data and in combination with the weighted normalized Euclidean distance for the computation of the separation measures of alternative(s) for the intuitionistic positive and negative ideal solutions. The two methods which have been used for the computation of the separation measure have been integrated using a new reflection defuzzification integration formula which has been introduced in this study. To prove the efficacy of the proposed model, the model have been applied for the evaluation and selection design concept for a new printed circuit board (PCB), and for a modified hypothetical example which is based on the selection of a preferred Naval vessel as a reference for a new design.